Domestic violence continues unabated : need for more interventions (2011)
Presents articles on an overview of the situation of domestic violence in Guyana, the drafting of a National Policy on Domestic Violence, the role of the Domestic Violence Policy Implementation Unit; gender-based violence; the function of the White Zone; the creation of an abusive Caribbean male and a commentary on male marginalisation.
Keywords: VIOLENCE AGAINST WOMEN